2007
DOI: 10.3171/spi.2007.6.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Discal cysts of the lumbar spine

Abstract: ✓Discal cysts are rare lesions that can result in refractory sciatica. Because they are so rare, their exact origin and details of the clinical manifestations are still unknown. The authors report on five men treated for discal cysts. The mean age of the patients at the time of the surgery was 32 years (range 25–38 years). All patients suffered from lower-extremity pain and the results of the straight leg–raising test were positive in all cases. Three patients reported motor weakness and four had senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 21 publications
2
59
0
Order By: Relevance
“…Histologically, intraspinal cysts of the facet and the ligamentum flavum are referred as ganglion or synovial cysts [22]. The difference between discal cysts and other intraspinal cysts is based on the presence of lining cells; however, their imaging and clinical features are similar [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histologically, intraspinal cysts of the facet and the ligamentum flavum are referred as ganglion or synovial cysts [22]. The difference between discal cysts and other intraspinal cysts is based on the presence of lining cells; however, their imaging and clinical features are similar [21].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in cases of doubtful diagnosis, surgery is performed to relieve the compression of the neural structures, as surgical treatment leads to symptom improvement, regardless of its origin [8,18]. In addition, intraoperative findings of the apparent connection between the corresponding disc and the cyst are also possible to differentiate discal cysts from other intraspinal cysts [8,21]. For these reasons mentioned above, we did not perform discography, and MRI was satisfactory for the management of the patients in our series.…”
Section: Radiologic Featuresmentioning
confidence: 97%
See 1 more Smart Citation
“…In our series, symptoms and signs were indistinguishable from a lumbar disc herniation, causing sciatica and nerve root tension because the cyst was located ventro-medially to the nerve root, compressing the root dorso-laterally. Because the differential diagnosis between discal cysts and other intraspinal cysts is based on the presence of lining cells surrounding the connective tissue, Nabeta et al emphasized any strict distinction between the two in the clinical diagnosis is not need [12]. Another literature by Chiba et al reported the importance of discography by which communication between the cyst and the corresponding disc was detected in their most cases [1].…”
Section: Discussionmentioning
confidence: 99%
“…Discal cysts arise from spinal discs [1,2,10,12]. As the cyst grows, particularly when it arises due to degenerative disc changes, it could cause radiculopathy, such as lumbar disc herniation.…”
Section: Introductionmentioning
confidence: 99%